Perjanjian Pinjam Meminjam Uang Antara Renternir Dengan Konsumen di Pasar Desa Adat Mengwi - Ni Ketut Diah Prihandani; Desak Gde Dwi Arini; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
The debts or lending money is one of those things that is never ended, in the practiced borrowed money related to loan shark and consumer borrowed to practiced of the money between loan shark and consumer, that is many to founded in Desa Adat Mengwi market which debt agrement among loan shark and consumer is agrement among the two parties is sometimes weaknes of law. So if a default occurs in this agrement it will be difficult to reselved, based on the problem, two problem statements can be formulated 1. How legitimate the loan agrement is between loan shark and consumer in the Desa Adat Mengwi market and, 2.What legal efforts will do if there is a default on consumers. In solving those problem, the settlement method used is an empirical research method. With research directly collecting data used through interview and used the sociology approach, from the result of real research. Legitimate lending and borroming agrements among loan shark and consumers in Desa Adat Mengwi market guided by justice, that is the evert of default between loan shark and consumer and debt agrement, this is the factor that from consumers thenselves and affort to solve that are used are non litigation or community.